2021
DOI: 10.3390/ph14030286
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Low Doses of β-Caryophyllene, Ascorbic Acid and d-Glucosamine on Human Chondrocyte Viability and Inflammation

Abstract: β-caryophyllene (BCP), a plant-derived sesquiterpene, has been reported to have anti-inflammatory and antioxidant effects. The purpose of this study is to evaluate the effects of BCP in combination with ascorbic acid (AA) and d-glucosamine (GlcN) against macrophage-mediated inflammation on in vitro primary human chondrocytes. Changes in cell viability, intracellular ROS generation, gene expression of pro-inflammatory mediators, metalloproteinases (MMPs), collagen type II and aggrecan were analyzed in primary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…In line with that, the extract had no impact on the secretion of IL1β in the supernatants of PBMCs. Yet, other authors reported that sesquiterpenes were able to have a chondroprotective effect by decreasing NFκB expression [27]. As terpenoids were found previously in L. sylvatica [20], a similar effect could have been expected.…”
Section: Discussionsupporting
confidence: 64%
“…In line with that, the extract had no impact on the secretion of IL1β in the supernatants of PBMCs. Yet, other authors reported that sesquiterpenes were able to have a chondroprotective effect by decreasing NFκB expression [27]. As terpenoids were found previously in L. sylvatica [20], a similar effect could have been expected.…”
Section: Discussionsupporting
confidence: 64%
“…In fact, in 2020, Rao Jiang-Yan et al showed how, through autophagic activation, BCP is able to alleviate cerebral ischemia/reperfusion injury in mice, highlighting its protective role in animal cells and vessels [ 28 ]. Experimental studies showed that BCP reduces pro-inflammatory mediators such as tumor necrosis factor-alfa (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), thus ameliorating chronic pathologies characterized by inflammation and oxidative stress [ 29 , 30 , 31 , 32 ]. In 2012, Ou Ming-Chiu et al recruited 48 women with primary dysmenorrhea with an NRS > 5.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, AA can stimulate anabolic processes as shown in vitro [ 55 , 56 ]. Furthermore, in a most recent in vitro study, the potency of AA to exert synergistic effects together with β-caryophyllene and d -glucosamine was reported by decreasing the expression of inflammatory molecules and increasing the expression of collagen type II and aggrecan [ 57 ]. In our study we used AA as the active comparator since (a) AA is a common vitamin used in OA supplements and (b) patients enrolled in the study could not be treated only with placebo (ethical issues could be risen).…”
Section: Discussionmentioning
confidence: 99%